Polymeric Nanoparticles with Neglectable Protein Corona. Issue 18 (6th April 2020) - Alberg, Irina; Kramer, Stefan; Schinnerer, Meike; Hu, Qizhi; Seidl, Christine; Leps, Christian; Drude, Natascha; Möckel, Diana; Rijcken, Cristianne; Lammers, Twan; Diken, Mustafa; Maskos, Michael; et al.
Abstract: The current understanding of nanoparticle–protein interactions indicates that they rapidly adsorb proteins upon introduction into a living organism. The formed protein corona determines thereafter identity and fate of nanoparticles in the body. The present study evaluates the protein affinity of three core‐crosslinked polymeric nanoparticles with long circulation times, differing in the hydrophilic polymer material forming the particle surface, namely poly( N ‐2‐hydroxypropylmethacrylamide) (pHPMA), polysarcosine (pSar), and poly(ethylene glycol) (PEG). This includes the nanotherapeutic CPC634, which is currently in clinical phase II evaluation. To investigate possible protein corona formation, the nanoparticles are incubated in human blood plasma and separated by asymmetrical flow field‐flow fractionation (AF4). Notably, light scattering shows no detectable differences in particle size or polydispersity upon incubation with plasma for all nanoparticles, while in gel electrophoresis, minor amounts of proteins can be detected in the particle fraction. Label‐free quantitative proteomics is additionally applied to analyze and quantify the composition of the proteins. It proves that some proteins are enriched, but their concentration is significantly less than one protein per particle. Thus, most of the nanoparticles are not associated with any proteins. Therefore, this work underlines that polymeric nanoparticles can be synthesized, for which a protein corona formation does not take place. Abstract : This work evaluates the protein affinity of three different core‐crosslinked polymeric nanoparticles, which are incubated in human blood plasma and separated by asymmetrical flow field‐flow fractionation (AF4). It demonstrates that some proteins get enriched, but their concentration is significantly less than one protein per particle underlining that protein corona free nanoparticles can be prepared. This is highly promising for applications in nanomedicine.